Nanotechnology in the defense industry : advances, innovation, and practical applications - Sharon, Madhuri; Rodriguez, Angelica Silvestre Lopez; Sharon, Chetna; Gallardo, Pio Sifuentes (Hoboken, New Jersey : Wiley, 2019)
This book will be about various aspects related to applications and use of knowledge of nanotechnology in promoting defense activities. The area in which scientists are focusing includes (i) nano-devices such as sensors, GPS & computers, chemical & biological weapons, nano-fabrics, bulletproof materials, nano-stealth coating, use of nanotechnology in various areas of aerospace. It is intended to cover available methodologies and understanding of technologies for these applications. Not only for destructive but also to improve medical and casualty, safety care for soldiers, and to produce lightweight, strong and multi-functional materials for use in body armour, both for protection and to provide enhanced connectivity will be covered.
Keywords: Nanomaterials; Thin Films, Surfaces & Interfaces; Homeland Security; Electronic books